2023
DOI: 10.3390/metabo13010130
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin, a Plant Flavonol Attenuates Diabetic Complications, Renal Tissue Damage, Renal Oxidative Stress and Inflammation in Streptozotocin-Induced Diabetic Rats

Abstract: Diabetes mellitus is a metabolic syndrome characterized by increased glucose levels, oxidative stress, hyperlipidemia, and frequently decreased insulin levels. The current research was carried out for eight consecutive weeks to evaluate the possible reno-protective effects of quercetin (50 mg/kg b.w.) on streptozotocin (STZ) (55 mg/kg b.w.) induced diabetes rat models. Various physiological, biochemical, and histopathological parameters were determined in control, diabetic control, and quercetin-treated diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Quercetin is ubiquitously present in vegetables, fruit, tea, and wine and has anti-inflammatory, anti-oxidative, and anti-carcinogenic properties that form the basis for potential benefits to overall health and disease resistance [ 20 ]. In addition, there are many studies focusing on the protective effect of quercetin against fibrosis [ 6 , 7 , 8 , 9 ]. Previous studies have reported that the early and late therapeutic administration of quercetin ameliorated silicosis in vivo [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin is ubiquitously present in vegetables, fruit, tea, and wine and has anti-inflammatory, anti-oxidative, and anti-carcinogenic properties that form the basis for potential benefits to overall health and disease resistance [ 20 ]. In addition, there are many studies focusing on the protective effect of quercetin against fibrosis [ 6 , 7 , 8 , 9 ]. Previous studies have reported that the early and late therapeutic administration of quercetin ameliorated silicosis in vivo [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a 3,3′,4′,5,7-pentahydroxy flavonol and a plant flavonoid found in edible fruits and vegetables [ 3 , 4 , 5 ]. Quercetin also has a suppressive effect on fibrosis [ 6 , 7 , 8 , 9 ]. Previous research has revealed that quercetin plays a role in silicosis by inhibiting macrophage senescence, possibly via the senescence-associated secretory phenotype (SASP) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation was measured by estimating the malondialdehyde (MDA) concentration, which was evaluated by the absorbance of color development with thiobarbituric acid. The absorbance of the resulting product was estimated at 532 nm, and the results are expressed in nmol/g [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the chronic inflammation can lead to cancer in target organs as well as several tissues via multiple pathways [42]. Various natural compounds show antiinflammatory potential via inhibiting the production of inflammatory mediators or related signalling molecules [43][44][45][46][47][48].…”
Section: Inflammationmentioning
confidence: 99%